Analisis Model Matematika dalam Menemukan Solusi Permasalahan Stunting Akibat Kesehatan Mental Masyarakat di Kabupaten Jeneponto - Hasmiati; Sri Auliyah S; Pratama, Muhammad Isbar; Ade Septiani Kusuma Dewi; Muh. Taufiqurahman; Nurul Sakinah (Universitas Cokroaminoto Palopo, 2024)
Stunting is a complex public health issue, often caused by various factors, including individual and community mental health aspects. This study aims to present a systematic solution to the problem of stunting through the analysis of a mathematical model that integrates mental health factors in the community. The research begins by identifying mental health factors contributing to the increase in stunting cases. Primary and secondary data are used to build a mathematical model that takes into account variables such as stress levels, depression, anxiety in the population, considering other factors like nutritional status and the environment. The simulation results from this mathematical model provide in-depth insights into the impact of mental health on stunting rates in the community. This research shows a percentage increase 1,78% that improved access to mental health services, education, and social support significantly reduces the stunting rate. Moreover, this model allows for the identification of the most effective intervention strategies, including government programs. By combining careful mathematical analysis with knowledge of mental health, this study makes a significant contribution to formulating appropriate policies and intervention strategies to reduce stunting rates in society.